2020
DOI: 10.48550/arxiv.2011.00854
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Strong Evaluation Complexity of An Inexact Trust-Region Algorithm for Arbitrary-Order Unconstrained Nonconvex Optimization

C. Cartis,
N. I. M. Gould,
Ph. L. Toint

Abstract: A trust-region algorithm using inexact function and derivatives values is introduced for solving unconstrained smooth optimization problems. This algorithm uses high-order Taylor models and allows the search of strong approximate minimizers of arbitrary order. The evaluation complexity of finding a q-th approximate minimizer using this algorithm is then shown, under standard conditions, to be O min j∈{1,...,q} ǫ −(q+1) jwhere the ǫ j are the order-dependent requested accuracy thresholds. Remarkably, this order… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
37
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(40 citation statements)
references
References 10 publications
3
37
0
Order By: Relevance
“…of finding approximate minimizers of arbitrary order. Exploiting ideas of [12,7], we have shown that its evaluation complexity is (in expectation) of the same order in the requested accuracy as that known for related deterministic methods [7,10].…”
mentioning
confidence: 77%
See 3 more Smart Citations
“…of finding approximate minimizers of arbitrary order. Exploiting ideas of [12,7], we have shown that its evaluation complexity is (in expectation) of the same order in the requested accuracy as that known for related deterministic methods [7,10].…”
mentioning
confidence: 77%
“…We have considered a trust-region method for unconstrained minimization inspired by [10] which is adapted to handle randomly perturbed function and derivatives values and is capable Appendix: additional proofs Proof of (3.12) Proof. Since σ(½ Λ c k ) belong to A k−1 , because the random variable Λ k is fully determined, assuming P r(½ Λ c k ) > 0, the tower property yields:…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This paper attempts to answer a simple question: how does noise in function values and derivatives affect evaluation complexity of smooth optimization? While analysis has been produced to indicate how high accuracy can be reached by optimization algorithms even in the presence of inexact but deterministic (1) function and derivatives' values (see [8,16,28,3,29,21,14]), these approaches crucially rely on the assumption that the inexactness is controllable, in that it can be made arbitrarily small if required so by the algorithm. But what happens in practical applications where significant noise is intrinsic and can't be assumed away?…”
Section: Introductionmentioning
confidence: 99%